To Study the REITs Investment in Affecting the Investor’s Confidence with Inflation Rate as the Intervening Variable in Malaysian Financial Market - Yeoh Wee Win Yeoh (MultiTech Publisher, 2023)
The research had proposed the quantitative study using the correlation analysis and regression analysis to combine producing the quantitative output to test for hypothesis before drawing the conclusion of the study. The results and findings of the study posed the evidence to suggest the significant of the inflation rate being the intervening variable within the regression model of the REITs investment return and the trading volume of the REITs investment, but the regression analysis failed to demonstrate the existence of the relationship between the two variables. With this, the outcome of the study had been concluded where the findings had provided the significant contribution to the development of the academic refenrece and drawing the relevance understanding towards the investment behavioural within the financial market in Malaysia.